Risk Communication And Clinical Handoffs Between Medical Laboratory Sciences, Nursing, Dentistry, And Pharmacy (The Review of Diabetic Studies, 2024)
Introduction: For patient safety and care continuity in multidisciplinary healthcare settings, it is important to have clear communication about risks and structure clinical handoffs between Medical Laboratory Sciences, Nursing, Dentistry, and Pharmacy. Communication difficulties during handoffs might result in errors, delays, and suboptimal outcomes (Almutairi et al., 2021; FATIMAH et al., 2024).Aim: The objective of this study is to evaluate the influence of interdisciplinary collaboration on risk communication and clinical handoffs among laboratory, nursing, pharmacy, and dental services, with an emphasis on patient safety, information accuracy, and quality of treatment.Methods: A mixed-method methodology was employed, integrating structured surveys, semi-structured interviews, direct clinical observations, and simulation-based scenarios to investigate the efficacy of communication and collaboration among healthcare professionals.Findings: Effective interprofessional collaboration improves the clarity, timeliness, and accuracy of clinical handoffs, decreases errors, and fosters coordinated patient care; however, systemic impediments, workload constraints, and ambiguous job delineation persist as problems.Conclusion: To reduce clinical risks, improve patient safety, and raise the quality of healthcare in Medical Laboratory Sciences, Nursing, Dentistry, and Pharmacy, it is important to improve risk communication and handoffs through collaboration between different fields, standardized protocols, and ethical practices.